1998
DOI: 10.3171/jns.1998.89.4.0533
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral monitoring by means of oximetry and somatosensory evoked potentials during carotid endarterectomy

Abstract: The results indicate that at least as measured with the INVOS3100A instrument, a decrease in rSO2 of -10 or more or a decrease below an rSO2 of 50 is indicative of cerebral ischemia of sufficient severity to decrease the amplitude of SSEPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 14 publications
1
46
1
2
Order By: Relevance
“…In adults, normal TOI values have been reported to range from 65% to 85%. 14,36 -41 Although a number of authors have compared NIRS with other techniques such as jugular bulb oxygen saturation (SjO 2 ), transcranial Doppler ultrasonography and somatosensory-evoked potential 15,37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] or with neurologic events, few have attempted to define an absolute threshold for ischemia. 13,14,16,17,46,[57][58][59] Most studies of this type using NIRS make no attempt to correct for extracranial contributions to signal changes.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, normal TOI values have been reported to range from 65% to 85%. 14,36 -41 Although a number of authors have compared NIRS with other techniques such as jugular bulb oxygen saturation (SjO 2 ), transcranial Doppler ultrasonography and somatosensory-evoked potential 15,37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] or with neurologic events, few have attempted to define an absolute threshold for ischemia. 13,14,16,17,46,[57][58][59] Most studies of this type using NIRS make no attempt to correct for extracranial contributions to signal changes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the issue of extracranial contamination in SO 2 monitoring remains a topic of considerable debate, particularly when SO 2 monitoring is used for recognition of cerebral ischemia during ICA and external carotid artery clamping (Duncan et al, 1995;Kirkpatrick et al, 1995;Beese et al, 1998;Samra et al, 2000;Takeda et al, 2000). Most investigators have also observed that the absolute changes of SO 2 after ICA clamping were highly variable from patient to patient (Beese et al, 1998;Cho et al, 1998;Grubhofer et al, 2000;Samra et al, 2000) and that the specificity of these values are not sufficient for satisfactory identification of patients suffering from severe cerebral ischemia during ICA clamping (Beese et al, 1998;Grubhofer et al, 2000). However, other investigators suggest that the intersubject variability in the absolute changes of SO 2 could be addressed by normalizing the data and recording the decrease in SO 2 after ICA clamping as a percentage of preclamp value (Cho et al, 1998;Samra et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Most investigators have also observed that the absolute changes of SO 2 after ICA clamping were highly variable from patient to patient (Beese et al, 1998;Cho et al, 1998;Grubhofer et al, 2000;Samra et al, 2000) and that the specificity of these values are not sufficient for satisfactory identification of patients suffering from severe cerebral ischemia during ICA clamping (Beese et al, 1998;Grubhofer et al, 2000). However, other investigators suggest that the intersubject variability in the absolute changes of SO 2 could be addressed by normalizing the data and recording the decrease in SO 2 after ICA clamping as a percentage of preclamp value (Cho et al, 1998;Samra et al, 2000). Such normalization would account for intersubject variability as well as allow comparisons between different investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral oxygen saturation values were evaluated with regard to three cutoff points that should reflect critically low oxygenation. The incidence and duration of decrease in rSO 2 values (cerebral desaturation) were recorded as any of the three following values for more than five consecutive minutes; (1) decrease in absolute rSO 2 values to less than 50%, (2) decrease in absolute rSO 2 values to less than 40%, and (3) a 20% decrease compared to individual baseline value [11].…”
Section: Physiologic Variables Measurementmentioning
confidence: 99%